Pengembangan Handout CEKAP sebagai Bahan Ajar Bahasa Arab untuk Siswa Kelas VI Madrasah Ibtidaiyah - Elyana Nur Alfiani (Alsina : Journal of Arabic Studies, 2022)
This study aims to develop Arabic teaching materials with handouts for Madrasah Ibtidaiyah students by conducting a needs analysis and validation/feasibility test of Arabic teaching materials with expert judgment. The development of this handout teaching material aims to make it easier to understand the Madrasah Final Examination (UAM) material. Data collection techniques using observation, questionnaires, interviews, and documentation. The research and development procedure was carried out following the stages proposed by Thiagarajan. The results showed that the CEKAP Handout (Quick Capture UAMBN) teaching materials that were developed were relevant to the needs of students in facing UAM. The development of Arabic teaching materials that were compiled based on the results of planning and design development with the themes of At-Ta'rÄ«f bi-al-Nafs, Al-AdawÄt al-MadrasÄ«yah, Aá¹£á¸¥Äb al-Mihnah, Al-Ê¿UnwÄn, AfrÄd al-Usrah, Al -Alwan. The CEKAP handout is 20 pages long. From the results of the validation, this teaching material proved to be valid, the results of the validation of design experts were 84% and the validation of material experts was 82%. The results of the class VI MIN 2 Pati trial showed 86%. From the results of data analysis through the t-test formula produces Tscore (3.175) â‰¥ Ttable (1.703) so that there are differences before and after students use handout teaching materials.